KASUS DISTRIBUSI DAN PENGGUNAAN FORMALIN DALAM PENGAWETAN KOMODITI IKAN LAUT SEGAR (STUDI KASUS DI KOTA BANDAR LAMPUNG) [Formaldehyde Distribution and Using for Preserving Fresh Fish (A Case Study in Bandar Lampung City)] - Dias Yusdianson Girsang; Azhari Rangga; Susilawati Susilawati (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
The purpose of this study was to identify the presence of formaldehyde in some fresh fish commodities and to trace formaldehyde distribution in Bandar Lampung City. The formadelhyde tests were done on the storage water of fresh fish samples. The study conducted in July to October 2013 was devided in two stages: a survey to fill out a questionnaire to a number of respondents, followed by sampling some storage water of fresh fish to be tested in the laboratory. The tests were carried out on 52 sampling points taken from the fishing boats in the fishing landing port (17 boats), fish supplier car from outside Bandar Lampung (6 cars) as well as some fish sellers in 5 traditional market in Bandar Lampung (29 sellers). By conducting a laboratory test using Formaldehyde Test Kit, there were 2 samples that were purple (positively contain formaldehyde), which were taken from 2 boats in fish landing port of Lempasing. Then the assertion test was carried out to the positive samples using chromotropic acid (SNI 01 – 2894 – 1992). The results showed that the samples positively contained formaldehyde indeed, which was characterized by a bluish purple color. Based on the survey results and tracking, there was a distortion of formaldehyde distribution in Bandar Lampung, where domestic industries (including fisherman) obtained formaldehyde illegally, either from End Users, a local manufacturer or drugstore/hospital/other health care facilities. Keywords: formaldehyde, fresh fish storage water, distribution distortion.